High molecular weight sodium hyaluronate improves survival of syndecan-1-deficient septic mice by inhibiting neutrophil migration. - Tuvshintugs Baljinnyam; Enkhtuya Radnaa; Casey M Ouellette; Christina Nelson; Yosuke Niimi; Clark R Andersen; Vsevolod Popov; Jae-Woo Lee; Donald S Prough; Perenlei Enkhbaatar (PLoS ONE)
Methods Sepsis was induced by cotton smoke inhalation followed by intranasal administration of Pseudomonas aeruginosa in female (> 6 months) Balb/c and syndecan-1 knockout mice. Survival of mice, lung capillary endothelial glycocalyx integrity, lung water content, and vascular hyper-permeability were determined with or without HMW-SH treatment in these mice. Effects of HMW-SH on endothelial permeability and neutrophil migration were tested in in vitro setting. Results In septic wildtype mice, we found a severely damaged pulmonary microvascular endothelial glycocalyx and elevated levels of shed syndecan-1 in the circulation. These changes were associated with significantly increased pulmonary vascular permeability. In septic syndecan-1 knockout mice, extravascular lung water content was higher, and early death was observed. The administration of HMW-SH significantly reduced mortality and lung water content in septic syndecan-1 knockout mice, but not in septic wildtype mice. In in vitro setting, HMW-SH inhibited neutrophil migration and reduced cultured endothelial cell permeability increases. However, these effects were reversed by the addition of recombinant syndecan-1 ectodomain. Conclusions HMW-SH reduced lung tissue damage and mortality in the absence of syndecan-1 protein, possibly by reducing vascular hyper-permeability and neutrophil migration. Our results further suggest that increased shed syndecan-1 protein levels are linked with the inefficiency of HMW-SH in septic wildtype mice.